Contribuições para uma abordagem das representações de gênero a partir da mimesis e da performance - Wagner, Bruna (2018)
Through by fictionalizations we construct concepts about the things present in the world where we live. The female body was also and it is the object of fictionalizations. Literature, as a representation mechanism, it has used many of these references to create images and reproduce stereotypes about women. Our work aims to show how these constructions have taken place. For this work, we use mainly authors as Wolfgang Iser (2013) and Judith Butler (2016). They converge at the idea that the represantations happen through performances, they are creations, in other words, they are not "natural". In this way, we seek to show the creation mechanisms of the fictions of the feminine and how they settled down.